PENGARUH BUKAAN RUANG TERHADAP SENSE OF SACRED SPACE JEMAAT (OBJEK STUDI: GEREJA ST. GABRIEL BANDUNG) - Novita, Dian; L. Lukman, Aldyfra (Jurnal Riset Arsitektur, 2023)
Abstract - St. Gabriel's Church is the house of God and a place for Catholics to worship Him. St. Gabriel Catholic Church has a concept that prioritizes the relationship between human and God; between human and other people; and between human and the environment. Spatial comfort is an important factor in supporting the atmosphere of worship, therefore St. Gabriel Church strengthens the concepts with the application of passive and ecological design. The concept is applied through transparency and openness of large church buildings to the environment, to optimize natural lighting and air conditioning. This makes the physical form of St. Gabriel Church looks different from the Catholic Church in general, which is relatively closed with limited openings, to minimize noise disturbances from outside in order to form a more sacred atmosphere of worship. The experience of the room in the church will affect the atmosphere of worship and the experience of spirituality of the congregation when carrying out worship activities. The atmosphere and use of space are not only perceived through visual sense, but also through auditory and olfactory sense. Therefore, this research is interesting to be conducted, in order to understand how a design opening in a sacred building can effecting the congregation’s sense of sacred space. This study applies qualitative – descriptive approaches. The data was collected by field observation, literature studies, and disseminating questionnaires to church congregations. The data is analyzed in accordance with the theoretical studies used and also from the results of questionnaires regarding the sense of sacred space of the congregation concerning the design of openings at St. Gabriel's Church. The results showed that the sense of sacred space of the congregation can be formed, with a calm and conducive atmosphere of worship space. The building openings have an important role in shaping that atmosphere. Therefore, it can be concluded that the visual and audial quality resulting from the openings, whereas their role as role as an audio – visuals buffer are greater than the role as a light filter, will create congregations’ sense of sacred space in the St. Gabriel’s Church. Keywords: Building Openings, Catholic Church, Sense of Sacred Space.